20th AIAA/CEAS Aeroacoustics Conference 2014
DOI: 10.2514/6.2014-2763
|View full text |Cite
|
Sign up to set email alerts
|

On LAGOON Nose Landing Gear CFD/CAA Computation over Unstructured Mesh using a ZDES approach

Abstract: This paper is part of ONERA's effort to compute the noise generation around landing gears, effort that has been shown with studies on a variety of configurations such as the ones included inside the BANC-II (Benchmark problems for Airframe Noise Computations). In this case, the addressed geometry is the LAGOON baseline nose landing gear. On the present computation, a refined unstructured mesh is generated for resolving the boundary layer up to y + around one. The simulation of the flow was performed using a Zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…To predict the far-field noise from obtained 2D near-field flow data, the missing data along the span can be compensated by assigning an SCL. For a variety of bluff body shapes at moderate to high Re, the flow was found to be fully correlated just along a few body diameters [39,[41][42][43].…”
Section: Proposed Approach For the Lg Far-field Noise Predictionmentioning
confidence: 95%
“…To predict the far-field noise from obtained 2D near-field flow data, the missing data along the span can be compensated by assigning an SCL. For a variety of bluff body shapes at moderate to high Re, the flow was found to be fully correlated just along a few body diameters [39,[41][42][43].…”
Section: Proposed Approach For the Lg Far-field Noise Predictionmentioning
confidence: 95%
“…The present computation is based on a previous computation performed with the CEDRE code on the same geometry, presented in reference [12]. A second hybrid grid is constructed based on the previous one, re-arranging the elements of the grid in order to obtain a refined grid with the same mesh metrics, hence the computational cost is expected to be comparable.…”
Section: Mesh Generationmentioning
confidence: 99%
“…However, the RANS/LES method is still very expensive for aeroacoustic prediction because of the large amount of high-resolved grids and long-time cost required by the LES simulation. A well-known benchmark study for a 2-wheel gear named LAGOON showed the comparisons between different CFD solvers for aeroacoustic 2 Mathematical Problems in Engineering prediction [3,9]. So how to predict the aeroacoustics with more efficiency with good accuracy is a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…There are mainly four types of numerical aeroacoustic prediction methods [5], including the pure theoretical method [6], the semiempirical method [7], the direct numerical method, and the hybrid method [3,8]. In particular, the Lattice-Boltzmann-Method (LBM) has shown being a very promising technique for far field aeroacoustic prediction (Benjamin Duda, Ehab Fares, 2017), such as LAGOON landing-gear configuration [9] and Jet-plate interaction noise [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation